Impact of Thermophoretic Transport of Al2O3 Nanoparticles on Viscoelastic Flow of Oil-Based Nanofluid over a Porous Exponentially Stretching Surface with Activation Energy - ETWIRE, Christian John; SEINI, Ibrahim Yakubu; RABIU, Musah; MAKINDE, Oluwole Daniel (Engineering Transactions, 2019)
The influence of thermophoretic transport of Al2O3 nanoparticles on heat and mass transfer in viscoelastic flow of oil-based nanofluid past porous exponentially stretching surface with activation energy has been examined. Similarity technique was employed to transform the governing partial differential equations into a coupled fourth-order ordinary differential equations which were reduced to a system of first-order ordinary differential equations and then solved numerically using the fourth-order Runge-Kutta algorithm with a shooting method. The results for various controlling parameters were tabulated and graphically illustrated. It was found that the thermophoretic transport of Al2O3 nanoparticles did not affect the rate of flow and heat transfer at the surface but it affected the rate of mass transfer of the nanofluid which decayed the solutal boundary layer thickness. This study also revealed that activation energy retards the rate of mass transfer which causes a thickening of the solutal boundary layer.